2020
DOI: 10.1016/j.redox.2019.101334
|View full text |Cite
|
Sign up to set email alerts
|

Altered inflammasome machinery as a key player in the perpetuation of Rett syndrome oxinflammation

Abstract: Rett syndrome (RTT) is a progressive neurodevelopmental disorder mainly caused by mutations in the X-linked MECP2 gene. RTT patients show multisystem disturbances associated with an oxinflammatory status. Inflammasomes are multi-protein complexes, responsible for host immune responses against pathogen infections and redox-related cellular stress. Assembly of NLRP3/ASC inflammasome triggers pro-caspase-1 activation, thus, resulting in IL-1β and IL-18 maturation. However, an aberrant activation of inflammasome s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 73 publications
4
23
0
Order By: Relevance
“…Primary cultures of dermal fibroblasts were obtained from 3‐mm skin biopsies taken during the periodic clinical checks‐up for the ASD patients or during health checks or by donations for the healthy donors. As previously described, 8 fibroblasts were cultured in Dulbecco's Modification of Eagle's Medium (DMEM) (cat. 10‐014‐CV, Corning, New York, NY, USA) supplemented with 10% of fetal bovine serum (FBS) (cat.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Primary cultures of dermal fibroblasts were obtained from 3‐mm skin biopsies taken during the periodic clinical checks‐up for the ASD patients or during health checks or by donations for the healthy donors. As previously described, 8 fibroblasts were cultured in Dulbecco's Modification of Eagle's Medium (DMEM) (cat. 10‐014‐CV, Corning, New York, NY, USA) supplemented with 10% of fetal bovine serum (FBS) (cat.…”
Section: Methodsmentioning
confidence: 99%
“…H1009, Sigma‐Aldrich, St. Louis, MO, USA) for different time points. Total, cytoplasmic and nuclear extracts were obtained as previously described 8 . Briefly, cells were lysed in Radio‐Immunoprecipitation Assay (RIPA) buffer (cat.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Little is known about the role of this cytokine in disorders linked to MeCP2 mutations; however, the role of the inflammasome and its products (IL-1 and IL-18) in RTT pathogenesis has been recently explored. Pecorelli et al demonstrated that fibroblasts isolated from RTT patients show an activated inflammasome machinery even under baseline conditions [46]. These data suggest that MeCP2 is an essential regulatory factor for the activation of the inflammasome and for preventing the perpetuation of an inflammatory state.…”
Section: Impaired Regulation Of Immune Mediators In the Cns Of Mecp2 mentioning
confidence: 97%